Design and Fabrication of Progressive Tool for Sheet Metal Component - Bhutani, Bhavil; Khera, Mohit; Rana, Rishabh; Sharma, Sachin; ., Dilip; Shakkarwal, Pankaj (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
The aim is to reduce the cost of the progressive dies without compromising on the quality of output. Using the optimum resources possible in designing the progressive dies frame can effect this reduction in the cost of the progressive dies.A progressive die performs a series of fundamental sheet metal operations at two or more stations during each press stroke in order to develop a work piece as the strip stock moves through the die. Each working station performs one or more distinct die operations but strip must move from the first station through each succeeding station to produce a complete part.The linear travel of the strip stock at each press stroke is called the “progression”, “advance” or “pitch” and is equal to the infestation distance. The main advantage of computer-aided progressive die design and machining is ability to build precision tooling in less time and at a lower cost.[Kumar et al… 2000]